β cell ER stress and the implications for immunogenicity in type 1 diabetes - Marre, Meghan L.; James, Eddie A.; Piganelli, Jon D. (Frontiers in Cell and Developmental Biology, 2015)
Type 1 diabetes (T1D) is a chronic autoimmune disease characterized by hyperglycemia due to progressive immune-mediated destruction of insulin-producing pancreatic islet β cells. Although many elegant studies have identified β cell autoantigens that are targeted by the autoimmune response, the mechanisms by which these autoantigens are generated remain poorly understood. Normal β cell physiology includes a high demand for insulin production and secretion in response to dynamic glucose sensing. This secretory function predisposes β cells to significantly higher levels of endoplasmic reticulum (ER) stress compared to nonsecretory cells. In addition, many environmental triggers associated with T1D onset further augment this inherent ER stress in β cells. ER stress may increase abnormal post-translational modification (PTM) of endogenous β cell proteins. Indeed, in other autoimmune disorders such as celiac disease, systemic lupus erythematosus, multiple sclerosis, and rheumatoid arthritis, abnormally modified neo-antigens are presented by antigen presenting cells in draining lymph nodes. In the context of genetic susceptibility to autoimmunity, presentation of neo-antigens activates auto-reactive T cells and pathology ensues. Therefore, the ER stress induced by normal β cell secretory physiology and environmental triggers may be sufficient to generate neo-antigens for the autoimmune response in T1D. This review summarizes what is currently known about ER stress and protein PTM in target organs of other autoimmune disease models, as well as the data supporting a role for ER stress-induced neo-antigen formation in β cells in T1D.